Calculation of Energy Band gap of Porous Silicon Based On The Carrier Transport Mechanisms - Alwan M.Alwan (Engineering and Technology Journal, 2007)
The energy bandgap of photoluminescence porous silicon is calculatedbased on the analysis of the current-voltage characteristics and themeasurements of the thermal activation energy of the zero bias and reversebias currents of PS/n-Si porous silicon diodes at different temperatures. The2.1 eV bandgap resulting from these electrical measurements agrees well with2 eV measured in PL spectra.